Pluralism and diversity from the Islamic perspective Pluralism and diversity from the Islamic perspective - Keadan, Taghread Yousf (Journal of Islamic Sciences, 2021)
The aim of this research is to clarify the phenomenon of pluralism and diversity in its various aspects, with a focus on Islam’s position on pluralism and diversity in its various types and divisions. The research also sought to address religious and political pluralism, cultural pluralism, economic pluralism and Islam’s position and outlook on it. The study is based on the descriptive and analytical approach that sheds light on pluralism and diversity from an Islamic perspective, and through the descriptive and analytical approach, the study will provide a description and analysis of the plurality and diversity in thought and culture from the application of Islamic thought. The research reached the following results: - Religious pluralism, or Islam’s view of pluralism in general, is the ideal solution to the problem of religious conflict in the world and to the peaceful coexistence of different religions. Diversity in Islamic society is the best evidence of Islam’s tolerance and its recognition that difference is a universal nature. Islam adopts political pluralism on condition that it be disciplined within the framework of commitment to the supremacy of Sharia and not deviating from its established principles. - Islamic economics is based on matters that other systems lack. It combines private and public ownership at the same time, considering that both of them are assets and each of them has its objectives and sources, provided that they are legitimate. Economic pluralism expresses the existence of more than one economic system in a single country, and Islamic law is concerned with the economic aspect.